The juvenile victimization questionnaire: psychometric properties and poly-victimization among Portuguese youth - Almeida, Telma Catarina (2021)
Submitted by Paula Saraiva (psaraiva@egasmoniz.edu.pt) on 2021-07-02T15:24:52Z No. of bitstreams: 1 Artigo_TAlmeida_2020_01_final.pdf: 273337 bytes, checksum: c0245dc534e0bd22390f36a226525ae6 (MD5)